基于优化解调与频谱校正技术的变速箱故障振动特征提取 - 罗振东 (Jixie chuandong)
The vibration research through the fatigue test of a gear box is described.Using the optimized demodulation based on multiple analytic band-pass filter,and the technology of discrete spectrum correction,the frequency spectrum analysis of gear box vibration signals is carried out.The features of some typical faults,such as profile error,shaft misalignment,and fatigue pitting of bearing are extracted.